Analysis of Legionella pneumophila serogroup 6 strains isolated from a hospital warm water supply over a three-year period by using genomic long-range mapping techniques and monoclonal antibodies. - Lück, P C (1991)
Over a period of 3 years, Legionella pneumophila serogroup 6 strains were isolated from warm water outlets and dental units in the Dental Faculty and from the Surgery and Internal Medicine Clinics at the University of Dresden, Dresden, Germany. In the bacteriological unit of the above-mentioned facility, L. pneumophila serogroups 3 and 12 were grown from warm water specimens. The medical facilities are located in separate buildings connected with a ring pipe warm water system. All L. pneumophila serogroup 6 strains isolated from the warm water supply reacted with a serogroup-specific monoclonal antibody, but not with two other monoclonal antibodies which are subgroup specific, reacting with other serogroup 6 strains. The NotI genomic profiles obtained by pulsed-field gel electrophoresis of 25 serogroup 6 strains isolated from the Dental Faculty over a 3-year period, 1 isolate from the Internal Medicine Clinic, and 4 strains from the Surgery Clinic were identical. Furthermore, all these strains hybridized with a 300-kb NotI fragment when a legiolysin (lly)-specific DNA probe was used. The NotI pattern, however, differed from those of six serogroup 6 strains of other origins, one serogroup 12 strain from the bacteriological unit, and another six unrelated strains of serogroups other than serogroup 6. L. pneumophila serogroup 6 strains which can be divided into only two subgroups by the use of monoclonal antibodies are differentiated in at least six NotI cleavage types obtained by pulsed-field electrophoresis.